2000
DOI: 10.1097/00005768-200004000-00012
|View full text |Cite
|
Sign up to set email alerts
|

EPO, red cells, and serum transferrin receptor in continuous and intermittent hypoxia

Abstract: We suggest that intermittent exposure to moderate normobaric hypoxia 12 h daily for 1 wk induces a similar stimulation of erythropoiesis as continuous exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 19 publications
10
37
0
1
Order By: Relevance
“…6 months). This observation is in line with a recent study showing a significant increase in TfR levels in short-term intermittent hypoxia on day 5-7 at high altitude (Koistinen et al 2000). We assume that partly acclimatization to long-term intermittent hypoxic exposure, as observed in OI, is not reached within the limited period of months experienced by SI.…”
Section: Iron Status and Erythropoietic Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…6 months). This observation is in line with a recent study showing a significant increase in TfR levels in short-term intermittent hypoxia on day 5-7 at high altitude (Koistinen et al 2000). We assume that partly acclimatization to long-term intermittent hypoxic exposure, as observed in OI, is not reached within the limited period of months experienced by SI.…”
Section: Iron Status and Erythropoietic Activitysupporting
confidence: 92%
“…about 5,400 m) followed by 1.5 min of room air for 4 h, Epo levels increased by about 50% after 6 h (Knaupp et al 1992), and (2) when alternately exposed for 12 h to 15.4% O 2 (e.g. 2,500 m in a normobaric flat) followed by 12 h in normal conditions for 7 days, Epo increased by about 70% after the 1st day (Koistinen et al 2000). Moreover, in a unique study, Gunga and coworkers (1996) demonstrated an approximate 3.5-fold increase in Epo in Chilean miners who worked regularly at 3,600-4,000 m for 10 days followed by 4 days rest at sea level over a period of 5 years.…”
Section: Iron Status and Erythropoietic Activitymentioning
confidence: 95%
“…Friedmann et al (1999) investigated members of the German national boxing team over 18 days at an altitude of 1800 m. They reported a significant increase in [EPO] without any change in total blood volume. Rapid elevations of [EPO] during moderate hypoxia, as in our volunteers, were also described by others (Gunga et al 1994a;Koistinen et al 2000). Koistinen et al (2000) investigated the effect of hypoxia in healthy subjects, who lived for 7 days under continuous or intermittent hypoxic conditions simulating an altitude of 2500 m. In both groups, a rapid and sustained increase in [EPO] was detected.…”
Section: Erythropoiesis Iron Metabolism and Angiogenesissupporting
confidence: 82%
“…Rapid elevations of [EPO] during moderate hypoxia, as in our volunteers, were also described by others (Gunga et al 1994a;Koistinen et al 2000). Koistinen et al (2000) investigated the effect of hypoxia in healthy subjects, who lived for 7 days under continuous or intermittent hypoxic conditions simulating an altitude of 2500 m. In both groups, a rapid and sustained increase in [EPO] was detected. In most altitude studies the rapid increase of [EPO] was accompanied by elevated reticulocyte counts within the first few days at altitude remaining above normoxic values during the altitude sojourn (Friedmann et al 1999;Koistinen et al 2000).…”
Section: Erythropoiesis Iron Metabolism and Angiogenesissupporting
confidence: 82%
“…Therefore, combining sTfR measurements into a multiparametric assessment of erythroid marrow function may improve the detection of rHuEpo abuse [50,51]. However, intermittent or continuous hypoxia [52] as achieved by a ''living high-training low'' program [53] also induce endogenous Epo-driven elevated sTfR values.…”
Section: Main Characteristicsmentioning
confidence: 99%